ASSEMBLING THE ISLAMIC MOSAIC OF THE SASAK TRIBE THROUGH TRADITIONAL CLOTHING - Hartini, Dina; Hidayati, Baiq Rosida; Rahmayani, Dwina; Nahdiah, Fadhilatul; Hariadi, Eka Putra; Saharudin, Saharudin (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2024)
The traditional clothing of the Sasak tribe is clothing that the people of Lombok usually wear at various events such as weddings, traditional ceremonies, or welcoming guests. Men's traditional clothing is called pegon, while women's traditional clothing is called lambung. When wearing traditional Sasak clothing, there are also several accessories such as keris, slewoq, dodot, and sapuq for men and pangkak, tongkak, and bendang/slewoq for women. The traditional clothing used by the Sasak tribe in daily life cannot be separated from religion, especially Islam which is the religion of the majority of the people of the island of Lombok. The aim of this research is to find out what Islamic meanings are contained in the traditional clothing of the Sasak tribe. This research is a type of qualitative descriptive research conducted in the Central Lombok area, specifically in Bebuak Village, Kopang District. The data collection techniques used in this research were direct observation and interviews. The research results show that there are many Islamic meanings contained in the traditional clothing of the Sasak-Lombok tribe, such as monotheism, purity, gentleness, tranquility, and so on. Thus, the traditional clothing of the Sasak-Lombok tribe not only has an aesthetic function but also has a religious function.